Compacting of Highly Dispersed ZrO[2](Y[2]O[3]) Powders - Burlachenko G.; Mirovoy Yu. A. Yury Aleksandrovich; Rygin A. V.; Buyakov A. S. Ales Sergeevich; Buyakova S. P. Svetlana Petrovna (2018, 2018)
Title screen